2004
DOI: 10.1021/ma049333x
|View full text |Cite
|
Sign up to set email alerts
|

Deformation-Induced Phase Transition and Superstructure Formation in Poly(ethylene terephthalate)

Abstract: Deformation-induced phase transitions and superstructure formation in poly(ethylene terephthalate) (PET) were studied by means of in-situ synchrotron small-angle X-ray scattering (SAXS) and wide-angle X-ray diffraction (WAXD) as well as Raman spectroscopy. The deformation conditions involved uniaxial stretching of quenched PET films at a temperature just below its glass transition temperature (T g), where a notable “plastic deformation” stage was observed. WAXD results indicated that the initial sample contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
146
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(158 citation statements)
references
References 48 publications
(114 reference statements)
11
146
1
Order By: Relevance
“…Some strain-induced new crystals insert into the original lamellae resulting in the reduced long period L, while those located out of the original lamellae orient from the weak oval ring to two-bar in SAXS pattern. In Hsiao's work [24,25], the strain-induced crystallization in the sporadic nucleation process is also reported, reckoning as lamellae insertion mechanism in PET system. The serial L, revealed by figure-8 pattern or X-shaped pattern, may also arise from long range order because some lamellae far apart can become more ordered and correlated under stretching.…”
Section: Lamella Development Under Deformationmentioning
confidence: 95%
See 2 more Smart Citations
“…Some strain-induced new crystals insert into the original lamellae resulting in the reduced long period L, while those located out of the original lamellae orient from the weak oval ring to two-bar in SAXS pattern. In Hsiao's work [24,25], the strain-induced crystallization in the sporadic nucleation process is also reported, reckoning as lamellae insertion mechanism in PET system. The serial L, revealed by figure-8 pattern or X-shaped pattern, may also arise from long range order because some lamellae far apart can become more ordered and correlated under stretching.…”
Section: Lamella Development Under Deformationmentioning
confidence: 95%
“…Along with the new evidence, the existing model was further improved and some hypotheses of lamellae slippage and melting-recrystallization were also introduced. From another point of view, phase transition triggered by stretching has also been extensively reported for many materials, such as polyamide (PA) [10,20,21], PP [17,22,23], and poly(ethylene terephthalate) (PET) [24,25]. These varying crystal structures may endow polymers with unique physical properties.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…This model is developed to capture the behavior of polymer near the glass transition temperature, with the following assumptions/limitations: (1) the effect of viscosity and change in viscosity are not significant at the temperature range in the rubbery state for which the model is developed, (2) within the valid temperature range, post-strain history can be simulated, though due to the difficulty in separating in-process and post-process experimental measurements, the post-strain behavior could be embedded within the model parameters, and (3) as crystallization proceeds, there is no net change in the combined orientation (between crystalline and amorphous regions) when polymer segments leave amorphous region to join crystalline domains; the decrease in orientation in the amorphous region due to this exchange will have a corresponding increase in orientation for the crystalline regions. Although there is some experimental evidence regarding the existence of an intermediate mesophase during SIC (Kawakami et al, 2005), it is not explicitly accounted as a separate phase in our formulation.…”
Section: Introductionmentioning
confidence: 99%
“…Imai et al 17 proposed an ordering process of crystallization induction prior to crystal nucleation, in which the ordering of chain segments increases the chain rigidity, and then the crystallization begins once a certain level of order is achieved. Kolb et al 18 described PET fiber structure development during melt spinning according to in situ X-ray diffraction measurements with a time resolution of 0.33-0.6 ms. Kawakami et al 19 observed, in batch drawing, a series of strain-induced phase transitions using X-ray diffraction measurements, including phase transitions from an isotropic slush to an oriented slush, from the oriented slush to smectic C, from smectic C to quasi-smectic A, and from quasi-smectic A to a triclinic crystal. Mahendrasingam et al 20 examined fiber structure development after batch drawing using X-ray diffraction data recorded over 40 ms.…”
Section: Introductionmentioning
confidence: 99%